Waste Cooking Oil Disposal Practices of Selected Restaurants in Subic Bay, Olongapo and Zambales - Abrajano, Rhia May C.; Gaspar, Lovely Ann G.; Fabro, Gwen Stefani R.; Ramos, Joeward N.; Rabago, Ray Mart A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The main purpose of the study was to determine the waste cooking oil disposal practices of selected restaurants in Subic-Olongapo, Zambales. There were 78 respondents from selected restaurants in Subic- Olongapo, Zambales. This study made use of descriptive-survey method. The test of validly and reliability were done to ensure that questionnaire gathered the necessary data for study. Data were analyze using various statistical methods. Results of the study showed that it is very common to the restaurants to dispose below 3 liters with 60.0% on a daily basis and for weekly basis the highest percentage of average volume disposal is 1 to 3 gallons with 17.1% and the monthly basis disposed below 5 gallons with 54.3%. The restaurant waste cooking oil practices disposal is rated “sometimes” with an overall mean of 1.67, (SD=0.73). In terms of disposed to sink, (M=1.19, SD=0.62), disposed to the drainage (M=1.21, SD=0.51), disposed to the garbage bin (M=1.69, SD=0.61), and collected by subcontractor’s agency (M=3.01, SD=1.00). The restaurant employees often attend orientation/seminar is organized by the restaurant/management staff (M=3.37, SD=0.75), followed by orientation/seminar organized by LGU (M=2.31, SD=1.00), orientation/seminar organized by NGO advocate Green House practices (M=1.76, SD=1.03), orientation/seminars organized by DENR for environmental protection (M=2.17, SD=1.17) and as rated “Sometimes”. There is no significant difference in waste cooking oil disposal practices when grouped according with profile variables, except year in operation. The management can pay attention to skilled people who have the knowledge and work experience, especially in the work place not just a college graduate. The restaurants should have a specific average volume of cooking oil that they have to consume for the daily, weekly and monthly basis.